“Implementación de una máquina automatizada destiladora de etanol para disminuir el tiempo del proceso y mejorar la calidad del producto.” - Pesantez Alvarez, Carlos Mauricio (2020)
The following work deals with the implementation of an automated ethanol distiller machine to reduce the time of the process and improve the quality of the product, investigating the processes of obtaining ethanol, the parameters for the control of the machine were determined, it was found that it was one of the first synthetic organic fermented products used by man, with the inquiry about the distillation process tells us how to separate liquids such as ethanol from the must by evaporation and condemnation with the boiling point of ethanol being 78.4°C, replacing the manual operation of man with industrial technology, with the implementation of automation instrumentation and an Arduino Uno microcontroller, sensors and actuators that through a closed loop temperature control system, to monitor and operate the process and production of heart ethanol of (60 to 80) v/v, once the automation was done, tests were carried out to fine-tune the optimum temperature range for continuous production and resource optimization, resulting in a 10% increase in the quality of alcohol degrees, a 60% fuel optimization and a 20% decrease in harvesting time, thus concluding the effectiveness of automation on artisanal processes.